Unconfined compressive strength of gypsum treated basaltic sand - Velasquez, Rekon E.; Azul, Kristian M. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The main objective of this study is to identify the optimum gypsum content percentage to be mixed with the soil sample. Basaltic sand is soil made by crushing basalt rocks and is very abundant in the Philippines. Preliminary tests were conducted in order to get the fundamental engineering properties of the sand such as specific gravity, gradation and soil classification. Gypsum plaster, more commonly known as Plaster of Paris (PoP), is not normally used as a soil additive for improving soil properties. In this study Plaster of Paris was mixed, as binding material, with basaltic sand and water. Three quantities of PoP (20%, 30% and 40% by mass) and three quantities of water content (20%, 25% and 30% by mass) were used to make the specimens, giving a total of 9 mixtures in total. Each mixture ratio was also tested for 2 curing periods (7 days and 14 days). Testing for the compressive strength of these soil specimens were done using a digital Universal Testing Machine (UTM). From the data gathered the unconfined compressive strength of the gypsum-treated basaltic sand increase with longer curing period. Moisture content has the opposite effect, as it decreases the compressive strength as its percentage increases. There was no optimum gypsum content observed, given the set gypsum contents tested, because the compressive strength continues to increase. It is recommended to use the 30% gypsum percentage because it offers a significant improvement in the strength and a workable setting time.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Soil -- Compression testing; Gypsum as soil amendment; Basaltic sand